Protein and Metalloprotein Distribution in Different Varieties of Beans (Phaseolus vulgaris L.): Effects of Cooking - Aline P. Oliveira; Geyssa Ferreira Andrade; Bianca S. O. Mateó; Juliana Naozuka (International Journal of Food Science)
Beans (Phaseolus vulgaris L.) are among the main sources of protein and minerals. The cooking of the grains is imperative, due to reduction of the effect of some toxic and antinutritional substances, as well as increase of protein digestibility. In this study, the effects of cooking on albumins, globulins, prolamins, and glutelins concentration and determination of Fe associated with proteins for different beans varieties and on phaseolin concentration in common and black beans were evaluated. Different extractant solutions (water, NaCl, ethanol, and NaOH) were used for extracting albumins, globulins, prolamins, and glutelins, respectively. For the phaseolin separation NaOH, HCl, and NaCl were used. The total concentration of proteins was determined by Bradford method; Cu and Fe associated with phaseolin and other proteins were obtained by graphite furnace atomic absorption spectrometry and by flame atomic absorption spectrometry, respectively. Cooking promoted a negative effect on (1) the proteins concentrations (17 (glutelin) to 95 (albumin) %) of common beans and (2) phaseolin concentration (90%) for common and black beans. Fe associated with albumin, prolamin, and glutelin was not altered. In Fe and Cu associated with phaseolin there was an increase of 20 and 37% for the common and black varieties, respectively.